Hati Nurani: Kesatuan Harmonis Antara Synderesis, Conscientia dan Keutamaan Kebijaksanaan - Benny Phang Khong Wing (Studia Philosophica et Theologica, 2021)
This article describes the meaning of conscience according to the definition presented by the Second Vatican Council in the light of Thomistic and Carmelite perspectives and explains the depth of this definition, in order to dispel misconceptions about the meaning of conscience that are widely circulated, and show its proper role in the edifice of moral theology. For this reason, this article elaborates on the harmonious correlation between the two dimensions of conscience, namely, synderesis and conscientia, as well as the harmonious correlation they have with the virtue of prudence which is perfected by the gift of counsel from the Holy Spirit. The pastoral aspect of this article is presented in the end by analyzing the importance of conscience revived by the Church as presented in the apostolic exhortation of Amoris Laetitia.